2016
DOI: 10.4038/rjs.v7i2.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Na<sub>2</sub>SiO<sub>3</sub> on heavy metal uptake by field grown <em>Basella alba</em> L. in Matara, Sri Lanka

Abstract: Abstract. In this study, we investigated heavy metal uptake and the effects of Na 2 SiO 3 on heavy metal absorption by field grown Basella alba L (Basellaceae). The concentrations of Fe, Cr, Pb and Cd in the field soils were 29755.30 ± 292.02, 32.99 ± 0.97, 26.01 ± 1.02, 0.13 ± 0.004 µg/g, respectively. These concentrations are significantly below the maximum permissible limits reported by FAO/WHO. Although Fe, Cr, Pb and Cd were present in the soil, only Fe was absorbed by B. alba; the tissue concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…When the pH > 10, free Fe ions were almost nonexistent, and Fe was mainly present in the form of dispersed fine hydrous oxide or hydroxide colloidal particles . At pH = 9.4–12.6, the hydrolysis product of Na 2 SiO 3 was the negatively charged SiO­(OH) 3 – , which had an obvious micelle structure and could not only adsorb but also effectively passivate the positively charged metal oxides and hydroxides, thus forming a stable colloidal solution . We can find that the solution after the reaction was a uniform red-brown liquid, and an obvious bright pathway appeared under laser irradiation, which indicated that the reaction solution was colloidal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the pH > 10, free Fe ions were almost nonexistent, and Fe was mainly present in the form of dispersed fine hydrous oxide or hydroxide colloidal particles . At pH = 9.4–12.6, the hydrolysis product of Na 2 SiO 3 was the negatively charged SiO­(OH) 3 – , which had an obvious micelle structure and could not only adsorb but also effectively passivate the positively charged metal oxides and hydroxides, thus forming a stable colloidal solution . We can find that the solution after the reaction was a uniform red-brown liquid, and an obvious bright pathway appeared under laser irradiation, which indicated that the reaction solution was colloidal.…”
Section: Resultsmentioning
confidence: 99%
“…23 At pH = 9.4−12.6, the hydrolysis product of Na 2 SiO 3 was the negatively charged SiO(OH) 3 − , 24 which had an obvious micelle structure and could not only adsorb but also effectively passivate the positively charged metal oxides and hydroxides, thus forming a stable colloidal solution. 25 We can find that the solution after the reaction was a uniform red-brown liquid, and an obvious bright pathway appeared under laser irradiation, which indicated that the reaction solution was colloidal. Therefore, it was presumed that a heterogeneous surface-catalyzed reaction initiated by the colloidal state of Fe occurred during the reaction.…”
Section: Role Of Free Radicalsmentioning
confidence: 89%